2021
DOI: 10.1557/s43577-021-00026-2
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-based vertically aligned nanocomposites for three-dimensional solid-state batteries

Abstract: Planar two-dimensional (2D) solid-state lithium-ion batteries exhibit an undesirable energy versus power balance, which can be dramatically improved by the application of three-dimensional (3D) geometries. Current ceramics-based nanocomposites exhibit limited control of the distribution and orientation of the nanoparticles within the matrix material. However, the tailoring of functionalities by the strong coupling between the two phases and their interfaces, present in epitaxial 3D vertically aligned nanocompo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…The collective concern across all techniques of Li-deficiency (highly volatile) is often counteracted with an overlithiation of the ceramic targets. , A more adaptable strategy to control the phase composition relies on the introduction of Li-rich targets (i.e., Li 2 O and Li 3 N) in the deposition sequence (e.g., multi-layering or co-deposition), which enjoys increasing popularity in the field of TFs. , This strategy enables the fabrication of complex compositional landscapes for the stabilization of the battery performance, such as dual-phases and nanocomposites . The first successful applications in the energy community and Li-ion batteries place greater attention on plural-phase nanocomposite structures and their beneficial stability for long-term applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The collective concern across all techniques of Li-deficiency (highly volatile) is often counteracted with an overlithiation of the ceramic targets. , A more adaptable strategy to control the phase composition relies on the introduction of Li-rich targets (i.e., Li 2 O and Li 3 N) in the deposition sequence (e.g., multi-layering or co-deposition), which enjoys increasing popularity in the field of TFs. , This strategy enables the fabrication of complex compositional landscapes for the stabilization of the battery performance, such as dual-phases and nanocomposites . The first successful applications in the energy community and Li-ion batteries place greater attention on plural-phase nanocomposite structures and their beneficial stability for long-term applications.…”
Section: Introductionmentioning
confidence: 99%
“…3,20−24 This strategy enables the fabrication of complex compositional landscapes for the stabilization of the battery performance, such as dual-phases 25 and nanocomposites. 26 The first successful applications in the energy community 27 and Li-ion batteries 28 place greater attention on plural-phase nanocomposite structures and their beneficial stability for long-term applications.…”
Section: Introductionmentioning
confidence: 99%
“…Although a range of epitaxial VANs has been studied in the last decade, lithium-based VANs for battery applications have remained primarily unexplored . Interestingly, two recent studies by Qi et al and Cunha et al demonstrated the unique potential of lithium-based VANs for achieving 3D solid-state batteries with enhanced energy storage performance.…”
Section: Introductionmentioning
confidence: 99%
“…[69,70] Additionally, filler alignment can create directional transport channels for facilitating the diffusion of thermal energy, [71,72] electrons, [73,74] and/or guest molecules, [75][76][77] leading to significant improvements in material performance compared to their randomly oriented analogues. [78][79][80] Therefore, development of polymer composites with oriented filler particles is important for many applications such as dielectric sensors/capacitors, [81][82][83][84] water purification, [85,86] energy storage, [87][88][89] and thermal management. [90][91][92][93] Directional assembly of fillers within the polymer matrix can be achieved through several strategies, including the use of compression force, [94,95] shearing, [96][97][98][99] and external fields, [100,101] which are applicable at an industrial scale.…”
Section: Introductionmentioning
confidence: 99%
“…[ 69,70 ] Additionally, filler alignment can create directional transport channels for facilitating the diffusion of thermal energy, [ 71,72 ] electrons, [ 73,74 ] and/or guest molecules, [ 75–77 ] leading to significant improvements in material performance compared to their randomly oriented analogues. [ 78–80 ] Therefore, development of polymer composites with oriented filler particles is important for many applications such as dielectric sensors/capacitors, [ 81–84 ] water purification, [ 85,86 ] energy storage, [ 87–89 ] and thermal management. [ 90–93 ]…”
Section: Introductionmentioning
confidence: 99%